Photoetching of Immobilized TiO2-ENR50-PVC Composite for Improved Photocatalytic Activity - M. A. Nawi; Y. S. Ngoh; S. M. Zain (International Journal of Photoenergy)
Commercially acquired TiO2 photocatalyst (99% anatase) powder was mixed with epoxidized natural rubber-50 (ENR50)/polyvinyl chloride (PVC) blend by ultrasonication and immobilized onto glass plates as TiO2-ENR50-PVC composite via a dip-coating method. Photoetching of the immobilized TiO2-ENR50-PVC composite was investigated under the irradiation of a 45 W compact fluorescent lamp and characterized by chemical oxygen demand (COD) analysis, scanning electron microscopy-energy dispersive X-ray (SEM-EDX) spectrometry, thermogravimetry analysis (TGA), and fourier transform infrared (FTIR) spectroscopy. The BET surface area of the photoetched TiO2 composite was observed to be larger than the original TiO2 powder due to the systematic removal of ENR50 while PVC was retained within the composite. It also exhibited better photocatalytic efficiency than the TiO2 powder in a slurry mode and was highly reproducible and reusable. More than 98% of MB removal was consistently achieved for 10 repeated runs of the photo-etched photocatalyst system. About 93% of the 20 mg L−1 MB was mineralized over a period of 480 min. The presence of SO42−, NO3−, and Cl− anions was detected in the mineralized solution where the solution pH was reduced from 7 to 4.